Early Experience with the HeartMate Percutaneous Heart Pump from the SHIELD II Trial. Issue 4 (8th July 2021) - Kapur, Navin K.; Jorde, Ulrich P.; Sharma, Samin; Pyo, Robert T.; Rajagopal, Vivek; Lotun, Kapildeo; Kimmelstiel, Carey; Kuo, Hai-Chien; Zhang, Zhen; Ying, Shih-Wa; West, Nick E. J.; Kandzari, David E.
Abstract : The HeartMate Percutaneous Heart Pump (PHP) is a novel circulatory support catheter delivering a self-expanding 24 French impeller across the aortic valve. The SHIELD II trial compares outcomes among heart failure patients undergoing high-risk percutaneous coronary intervention (HR-PCI) with the PHP versus Impella systems. The trial was halted in 2017 due to device malfunctions. We aimed to describe procedural, hemodynamic, and clinical outcomes among HR-PCI patients treated with PHP as part of the SHIELD II trial roll-in phase. Procedural, hemodynamic, and 90 day outcomes were assessed among patients undergoing HR-PCI with a left ventricular ejection fraction ≤35% and last patent coronary conduit, unprotected left main disease, or significant three vessel disease. The primary endpoint was the 90 day composite of cardiovascular death, myocardial infarction, stroke, repeat revascularization, major bleeding, new/worsening aortic regurgitation, and severe hypotension. Among 75 roll-in phase patients, PHP support duration was 101 ± 53 minutes with 2.5 ± 1.4 coronary lesions treated per patient. Compared with predevice values, the PHP system increased cardiac power and mean arterial pressure. Maximum recorded device flows were 0.4–6.2 L/minute with 26% ( n  = 19/73) and 9.6% ( n  = 7/73) of patients achieving peak flows above 3.5 or 5.0 L/minute, respectively. Five PHP device malfunction events (6.7%) were observed. At 90 days, the composite endpoint occurred in 24.3% (18/74) of patients. Early PHP experience demonstrated successful device performance in the majority of enrolled patients; however, unexpected malfunctions led to device revision. Completion of the SHIELD II trial will be required to confirm the safety and efficacy of this iteration of the PHP system in HR-PCI.